Metallic PCM-integrated solid oxide fuel cell stack for operating range extension. (1st March 2022) - Promsen, Mungmuang; Selvam, Kalimuthu; Komatsu, Yosuke; Sciazko, Anna; Kaneko, Shozo; Shikazono, Naoki
Highlights: Novel concept of metallic phase-change material (mPCM)-integrated SOFC is proposed. Uniform temperature profile is achieved even with high air utilization of 85%. mPCM suppresses temperature fluctuation of SOFC in load variation. mPCM-SOFC can operate at severe loads such as very high current density or shutdown. mPCM can be used to preheat inlet gas directly from room temperature. Abstract: A novel concept of integrating metallic phase-change materials (mPCMs) into solid oxide fuel cell (SOFC) stack is proposed with the aim to improve the thermal conditions and to enhance the flexibility of SOFC operation. A three-dimensional computational fluid dynamics modeling with electrochemistry and melting/solidification solver is used to demonstrate various operating scenarios of the mPCM-SOFC stack including drastic load variations such as rapid ramp-up and shutdown. Pure aluminum and copper-silicon-manganese eutectic alloy are evaluated as the potential mPCMs. The results show that the mPCM can improve the temperature distribution of the SOFC stack and enables the use of exceptionally high air utilization of 85%, which can reduce the parasitic loss of the air blower. The mPCM can suppress the temperature variation of the stack when the load is drastically changed. Melting of PCM can prolong the operation at peak-load by absorbing large heat generation, while solidification of PCM can sustain the stack temperature at part-load and shutdown conditions. The mPCM can also function as the inlet gas preheater, enabling direct feeding of room-temperature fuel and air into the stack, enhancing the cooling behavior.